Assessment of the efficacy of glyceryl trinitrate patch as a tocolytic - Mogri, Sushma; Choudhary, Lata; Verma, Anjana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Preterm labor is defined as onset of delivery after the age of gestational viability (20-28 weeks) and prior to 37 weeks. Preterm birth complicated 5-10% of all births and accounts for 75% of perinatal deaths. Several drugs are now available to delay delivery in spontaneous preterm labour. Delaying the delivery for at least 24-48 hr for lung maturity of fetus is the primary goal. Glyceryl trinitrate has less maternal side effects. Methods: The study included 100 women who were admitted in view of preterm labour with gestational age between 28-36 weeks and were given trans dermal nitroglycerin therapy for arrest of preterm labour. Results: The efficacy of nitroglycerine patch to arrest preterm labour was studied. 88 patients were successfully progressed for more than 48 hours with minimum prolongation of 3 days and maximum prolongation of 65 days and average prolongation of 26 days of pregnancy. Conclusions: Glyceryl trinitrate patch as a tocolytic is very effective. This drug has a good patient acceptability and compliance due to its minimal side effects, low cost and simple dosage schedule.